2020
DOI: 10.1177/0309364620906272
|View full text |Cite
|
Sign up to set email alerts
|

Self-directed usage of an in-home exergame after a supervised telerehabilitation training program for older adults with lower-limb amputation

Abstract: Background: While home-based exergames help overcome accessibility barriers to rehabilitation, it is unclear what constitutes effective intervention design in using exergames to support self-efficacy and engagement. Objective: Examine usage of an in-home exergame, compared to control, unsupervised after supervised training by older persons with lower-limb amputation. Study design: Secondary analysis of a multi-site parallel evaluator-masked randomized control trial. Methods: WiiNWalk uses the WiiFit and teleco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…In a feasibility study paired with this same framework, Tao et al compared supervised and unsupervised training in the home via telehealth. Similar to the results of Imam et al, researchers found that participants used the exergame less frequently when they were unsupervised in their home 45 . That being said, despite a decrease in frequency, the duration of this training was therapeutically sufficient 45 .…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In a feasibility study paired with this same framework, Tao et al compared supervised and unsupervised training in the home via telehealth. Similar to the results of Imam et al, researchers found that participants used the exergame less frequently when they were unsupervised in their home 45 . That being said, despite a decrease in frequency, the duration of this training was therapeutically sufficient 45 .…”
Section: Discussionsupporting
confidence: 61%
“…Similar to the results of Imam et al, researchers found that participants used the exergame less frequently when they were unsupervised in their home. 45 That being said, despite a decrease in frequency, the duration of this training was therapeutically sufficient. 45 Therefore, although there is promising evidence that telehealth can be used effectively in the home, participant adherence appears to be relatively low.…”
Section: Mobility Continuationmentioning
confidence: 95%
See 1 more Smart Citation
“…Beyond cardiovascular exercise, such games are of therapeutic interest for their involvement of psychomotor skills and even cognitive skills. Yet, the principal appeal behind using games for therapy, whether HMD-based or not, has been their potential to support sustained adherence to therapy [27][28][29]. As such, game-based therapy may be viewed as an approach to behavior change [30].…”
Section: Applying Gaming and Hmd-vr In Healthmentioning
confidence: 99%
“…23 The Home exercise or the home training are experiences of motor activities widely used in the context of strategies for increasing physical activity levels: in fact, in the literature, it is possible to find numerous studies that analyze the motor activity carried out within the home. This activity is mainly carried out by subjects with pathologies, [26][27][28][29][30] by subjects who have undergone transplants or prostheses, 31,32 by subjects who have undergone amputations 33 or as a motor activity with specific prevention programs. 34,35 Until now in Italy, due to the cultural characteristics of the adult and elderly population, on the contrary, this type of activity has not had a significant diffusion, both for the home training modalities and for the modalities that included motor activities supervised by experts.…”
mentioning
confidence: 99%